Red/purple leaf margin coloration: Potential ecological and physiological functions - Hughes, Nicole M.; Lev-Yadun, Simcha (Environmental and experimental botany, 2015)
•Red/purple leaf margins can be a constitutive trait or a stress response in plants.•The function of colored margins is unknown, and potential benefits are discussed.•Pigments may signal enhanced defenses at the leaf margin or highlight previous damage.•Photoprotection is discussed within the context of abiotic stress at the leaf margin.•Additional functions may include chelation of heavy metals or toxic trace elements. Leaf margins of many plant species belonging to the floras of several continents feature a conspicuous band of red/purple color around their periphery. Despite the widespread distribution of this leaf trait, very few studies have proposed or tested hypotheses to explain its significance (if any). Common explanations for leaf coloration, such as photoprotection, plant camouflage, attraction of seed dispersers, or undermining herbivorous insect camouflage do not seem, at first glance, to be applicable to this color pattern. Could pigments localized at the leaf margin still function in these traditional ecological or physiological roles? Or should new hypotheses be devised that are more specific to coloration at the leaf margin? The purpose of this paper is to review and explore potential ecological and physiological functions of pigmented leaf margins, in hopes of inspiring further inquiry into this topic.